2015
DOI: 10.1371/journal.pone.0120975
|View full text |Cite|
|
Sign up to set email alerts
|

Interspecific and Geographic Variation in the Diets of Sympatric Carnivores: Dingoes/Wild Dogs and Red Foxes in South-Eastern Australia

Abstract: Dingoes/wild dogs (Canis dingo/familiaris) and red foxes (Vulpes vulpes) are widespread carnivores in southern Australia and are controlled to reduce predation on domestic livestock and native fauna. We used the occurrence of food items in 5875 dingo/wild dog scats and 11,569 fox scats to evaluate interspecific and geographic differences in the diets of these species within nine regions of Victoria, south-eastern Australia. The nine regions encompass a wide variety of ecosystems. Diet overlap between dingoes/w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 133 publications
4
71
0
Order By: Relevance
“…That we did not observe the same relationship here may be because we only assessed the potential benefits of mesopredator suppression for two prey species. Given the many potential prey species in the study region (Davis et al., ), such benefits may be present for other, unstudied species (e.g. Mallee ningaui Ningaui yvonneae , western pygmy possum Cercartetus concinnus ).…”
Section: Discussionmentioning
confidence: 99%
“…That we did not observe the same relationship here may be because we only assessed the potential benefits of mesopredator suppression for two prey species. Given the many potential prey species in the study region (Davis et al., ), such benefits may be present for other, unstudied species (e.g. Mallee ningaui Ningaui yvonneae , western pygmy possum Cercartetus concinnus ).…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to account for potential prey switching by cats and foxes from rabbits to reptiles and invertebrates, due to a lack of empirical data. Likewise, the diet of dingoes is known to be broad, varying in different ecosystems, sometimes including mammalian prey in the critical weight range of 35–5,500 g. However, on average, dingoes typically consume orders of magnitudes fewer critical weight range mammals than do invasive mesopredators (e.g., Davis et al., ). Thus, to simulate the main interactions and community structure in the arid Australian ecosystem, the potential (but negligible) trophic interaction between the dingo and small native mammal prey was not incorporated into the model, preventing any potential prey switching to small native mammals by dingoes.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of scats collected in Victoria has shown that deer are eaten by wild dogs (Canis familiaris) and dingoes (Canis dingo) and their hybrids, and also by red foxes (Vulpes vulpes; Davis et al 2015b). Camera traps have shown that wild dogs and foxes scavenge hunter-shot sambar carcasses (Forsyth et al 2014).…”
Section: Interactions With Predatorsmentioning
confidence: 99%